Effect of Chronic Illness on Psychological Resilience in Adults in Indonesia - Indah, Maya (International Journal of Psychology, 2024)
Purpose: The aim of the study was to analyze the effect of chronic illness on psychological resilience in adults in Indonesia. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Recent research on the effect of chronic illness on psychological resilience in adults in Indonesia indicates that chronic illnesses significantly impact psychological well-being and resilience. Studies reveal that individuals with chronic conditions often experience decreased resilience due to increased stress and reduced coping abilities. However, factors such as strong social support, effective coping strategies, and access to mental health resources can mitigate these negative effects. For instance, patients with robust social networks and adaptive coping mechanisms show higher levels of psychological resilience despite their chronic conditions. Unique Contribution to Theory, Practice and Policy: Stress and coping theory, conservation of resources (COR) theory & self-determination theory (SDT) may be used to anchor future studies on the effect of chronic illness on psychological resilience in adults in Indonesia. Healthcare providers should implement resilience training programs that equip individuals with chronic illnesses with practical skills to enhance their psychological resilience. Policymakers should integrate psychological resilience into chronic illness management policies by mandating the inclusion of mental health support as a core component of chronic disease care.